2020
DOI: 10.4103/jets.jets_89_19
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric risk of mortality III score – Predictor of mortality and hospital stay in pediatric intensive care unit

Abstract: Background: Pediatric Risk of Mortality (PRISM) III score is one of the widely used scoring systems to quantify critical illness in the pediatric age group. This study was carried out to find the association of PRISM III score with the outcome (discharge/mortality) and also hospital stay in survivors and nonsurvivors. Setting: The study was conducted in a tertiary care hospital from January 2014 to June 2015. Materials and Methods: A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The mean PRISM-III was significantly higher in non survivors as compared to survivors. This is similar to studies from Brazil 16 , where the mean scores were 7 and 15, Portugal 10 , where the scores were 5.6 and 19.7 and an Indian study 17 , where the scores were 5.72 and 19.01 among survivors and non survivors respectively. A PELOD-2 score of >15, associated with increased risk of mortality in our study, was also observed in other studies 11 .…”
Section: Discussionsupporting
confidence: 84%
“…The mean PRISM-III was significantly higher in non survivors as compared to survivors. This is similar to studies from Brazil 16 , where the mean scores were 7 and 15, Portugal 10 , where the scores were 5.6 and 19.7 and an Indian study 17 , where the scores were 5.72 and 19.01 among survivors and non survivors respectively. A PELOD-2 score of >15, associated with increased risk of mortality in our study, was also observed in other studies 11 .…”
Section: Discussionsupporting
confidence: 84%
“…A total of 29 studies were included for quantitative synthesis, among them, 18 studies that reported on the scoring systems PRISM-III/IV, ( 3 , 4 , 11 , 14 – 21 , 23 27 , 37 ), 11 studies that reported data on PIM-3 ( 3 , 4 , 7 , 14 , 16 , 18 , 20 , 28 – 31 ), and nine studies that reported data on PELOD-2 ( 5 , 14 , 16 , 28 , 32 36 ). Four studies were reported from India ( 4 , 7 , 17 , 34 ), two from Australia ( 20 , 32 ), two from China ( 20 , 32 ), two from Egypt ( 15 , 18 ), one from Pakistan ( 19 , 26 ), two from Korea ( 14 , 36 ), one from Mexico ( 21 ), one from Singapore ( 28 ), one from UAE ( 29 ), one from Indonesia ( 30 ), one from Africa ( 33 ), one from Saudi Arabia ( 11 ), two from Turkey ( 22 , 24 ), one from Sweden ( 23 ), one from Brazil ( 37 ), one from Switzerland ( 5 ), one from Thailand ( 27 ), one from Italy ( 31 ), and one multi-centric ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…PRISM III is the most widely used pediatric critical care score. Kaur's study proved that it is capable of accurately determining the severity of the disease and predicting prognosis ( 20 ). Mayordomo-Colunga et al's study found that higher PRISM III was associated with non-invasive ventilation treatment failure ( 21 ).…”
Section: Discussionmentioning
confidence: 99%